Van Effen, Spectators, and The Republic of Letters in 1723 - James L Schorr (Etudes Epistémè)
After a little more than a decade of existence in English and in French, “Spectators” experienced a reevaluation from critics of Marivaux’s Spectateur français.  The rather heated discussion that ensued produced a rational, critical method for journalists to consider works of literature and inspired a number of new “Spectators” in French, among them Le Nouveau Spectateur français (1723-25) by the journalist-critic Justus van Effen.